Efeito da adição do LH durante o estímulo ovariano e maturação oocitária no perfil lipídico de oócitos murinos - Oleinki, Talitha Dinardo [UNIFESP] (2016)
Introduction: The addition of LH in assisted reproduction aiming to obtain a higher number of viable follicles for the treatment is still controversial. A good embryonic development depends on the follicular growth and proper oocyte maturation. Because of that, the association between alkaline comet assay and the study of oocyte lipidomics may help to understand the biological processes involved in oocyte maturation and the influence of hormonal protocol. This study may contribute in the future with effective hormonal protocols, improving the quality of oocytes and pregnancy rates. Objective: Evaluate the effect of adding LH on DNA integrity of cumulus cells and on lipid profile of murine oocytes. Methods: Female mice C57BL / 6J 23 to 28 days old received three different stimulation protocols intraperitoneally (i.p.): (i) only PMSG; (ii) PMSG plus hCG (iii) PMSG plus LHr. After 48 hours of administration, immature oocytes were collected and cultured for 24 hours in three different culture medium for maturation: (i) only FSH; (ii) FSH plus hCG (iii) FSH plus LHr. After this period, the oocytes which had the first polar body were frozen at -80oC until the analysis by electrospray ionization (ESI) and cumulus cells were subjected to alkaline comet technique to measure the integrity of DNA. The principal component analysis and discriminant analysis by least squares were performed and 35 ions with greater representation were identified by the variable importance in the projection. Results: There was no statistical difference in the maturation rate and DNA fragmentation of cumulus cells in different groups analyzed. The fingerprinting analysis of the lipid profile of oocytes matured in vitro identified twenty lipids. The hyper-represented lipids in the group stimulated with the addition of hCG and matured in culture medium only with FSH (HF group) are: phosphatidylethanolamine, polyketide (flavonoid), sterol, phosphatidylserine, polyketide (ansamycin), sphingomyelin and phosphatidylcholine; in the group stimulated and matured in the presence of hCG (HH group) phosphatidylglycerol, phosphatidylserine, sphingolipids and triacylglycerol are hyper-represented; and in group stimulated with addition of LHr and matured in culture medium only with FSH (LF group) the polyketide (flavonoid) and sphingolipids are hyper-represented. Conclusion: The protocol used for hormonal stimulation and MIV modify the lipid profile of the oocyte, but does not alter the oocyte maturation rate and the DNA integrity of cumulus cells.